Education Management for Islamic Teacher in the Digital Era: Integrating Innovation and Child Development Needs - Nur Cholid; Fadly Usman; Dwi Bhakti Indri; Azman Haji Kassim; Nuur Halimatus Saadiah Masrukhin; Rahmat Rahmat; Maidatus Sholihah (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
The digital era has transformed the way children interact with the world, including in the context of early childhood education (ECE). This study examines the principles of sound early childhood education in the digital era, including the role of technology, social interaction, and the roles of educators and parents in supporting children's learning. Emphasis is placed on the importance of balancing technology use with the development of children's socio-emotional, cognitive, and motor skills. This study uses a quantitative descriptive approach utilizing the SAMR (Substitution, Augmentation, Modification, Redefinition) framework to evaluate technology integration in ECE learning in Mojokerto. Data were collected through a Likert-scale questionnaire from 55 ECE teachers and analyzed to determine the extent to which the implementation of technology supports learning transformation. This study also employed SEM-PLS to examine the respondents' answers and the relationships between variables. More respondents were needed for the SEM-PLS analysis because the study included more than three constructs. For the SEM PLS analysis, the sample consisted of 158 ECE teachers. The results indicate that, although challenges remain in the initial stages of substituting and redesigning learning, most teachers demonstrate a high acceptance of the use of innovative technology that supports child engagement. This study provides practical and conceptual insights for educators and policymakers in designing learning strategies that align with digital development and children’s developmental needs.